Analysis of Tiktok Usage, Characteristics, and Learning Concentration Among Elementary School Students - Sri Ramadhani; Wahyullah Alannasir; Abrina Maulidnawati (ALENA : Journal of Elementary Education, 2026)
This research is motivated by the rapid use of TikTok social media among elementary school students, which raises concerns about the development of their ethical values and academic focus on learning. This study aimed to analyze the use of TikTok social media and its impact on the character and learning concentration of students at elementary school and the primary focus of this study is the students elementary school. The method used was descriptive qualitative with data collection techniques through observation, interviews, and documentation of students, teachers, and parents. The results show that students use TikTok for self-existence, creativity, and as a learning resource. TikTok usage has a dual impact on character: it has a positive influence on self-confidence and art skills but a negative impact on the use of impolite language if not supervised. Meanwhile, students' learning concentration tends to decrease, marked by a short focus duration (only ten to twenty minutes) and easily distracted due to being accustomed to fast short video stimulation. The conclusion of this research confirms that TikTok usage is negatively correlated with learning concentration and requires a synergy of supervision and guidance from teachers and parents so that the use of digital media remains educational and does not damage students' character.